Synergetic effect of sewage sludge and biomass co-pyrolysis: A combined study in thermogravimetric analyzer and a fixed bed reactor. (15th June 2016) - Wang, Xuebin; Deng, Shuanghui; Tan, Houzhang; Adeosun, Adewale; Vujanović, Milan; Yang, Fuxin; Duić, Neven
Highlights: The synergetic effect of sewage sludge and wheat straw co-pyrolysis was studied. The mass balance measurement of gas, tar, and char was performed. The synergetic effect shows strongest under a certain biomass addition ratio around 60%. The required heat of co-pyrolysis is significantly reduced. Abstract: Much attention has been given to the valuable products from the pyrolysis of sewage sludge. In this study, the pyrolysis of sewage sludge, biomass (wheat straw) and their mixtures in different proportions were carried out in a thermogravimetric analyzer (TGA) and fixed-bed reactor. The effects of pyrolysis temperature and percentage of wheat straw in wheat straw–sewage sludge mixtures on product distributions in terms of gas, liquid and char and the gas composition were investigated. Results indicate that there is a significantly synergetic effect during the co-pyrolysis processes of sewage sludge and wheat straw, accelerating the pyrolysis reactions. The synergetic effect resulted in an increase in gas and liquid yields but a decrease in char yield. The gas composition and the synergetic effect degree are strongly affected by the wheat straw proportions, and the strongest synergetic effect of sewage sludge and wheat straw co-pyrolysis appears at the biomass proportion of 60 wt.%. With an increase of temperature, the gas yield from the pyrolysis of sewage sludge increased but the liquid and char yields decreased. Moreover, the required heat of co-pyrolysis is significantly reduced compared with the pyrolysis of sewage sludge and wheat straw pyrolysis alone, because of the exothermic reactions between the ash components in two fuel samples.